Impact of Remote Work on Employee Productivity and Work-Life Balance : A Quantitative Study Examining Personal Boundary-Setting Strategies and Organizational Support in Remote Work Environments - Paudel, Aruna (My University, 2026)
The thesis explores the relationship between personal boundary-setting strategies and organizational support to employee productivity and work-life balance in the context of remote work. Based on Boundary Theory (Nippert-Eng, 1996; Clark, 2000), and Conservation of Resources (COR) Theory (Hobfoll, 1989), quantitative, cross-sectional survey was sent to 90 remote and hybrid workers in various industries and countries. The analysis of the data was done by descriptive statistics, Pearson correlation analysis and hierarchical multiple regression in IBM SPSS Statistics (Version 27). Results indicate that organizational support is the strongest and statistically significant predictor of employee productivity (β = .627, p < .001) and work-life balance (β = .498, p < .001), explaining about 29–30% of the incremental variance in both outcomes over and above the variance explained by the demographic variables. There was a significant bivariate relationship between personal boundary-setting strategies and work-life balance (r = .445, p < .001) but this was not found to be significant in regression models after controlling for organizational support. There was no significant association between the bivariate nor regression analysis for boundary-setting strategies and employee productivity. The findings corroborate what COR Theory predicts that institutional condition resources are the most important factors in determining remote work outcomes and indicate that individual coping strategies are dependent on the organizational resource environment, but not independently so. Formal remote work policies are recommended, along with enhanced communication skills for managers and active employee recovery time protection.
Keywords: remote work; working life; remote management; employees; efficiency (properties); COVID-19; well-being at work; work; leadership (activity); pandemics; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development